2011
DOI: 10.2105/ajph.2011.300265
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Community Capacity to Participate in Making Decisions to Reduce Disproportionate Environmental Exposures

Abstract: Environmental exposures impose a disproportionate health burden on low-income populations and communities of color. One contributing factor may be the obstacles such communities face to full participation in making policy decisions about environmental health. This study described and analyzed the characteristics that contributed to communities' capacity to participate in making environmental decisions and suggested steps public agencies could take to achieve more meaningful participation. By strengthening comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
86
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 47 publications
3
86
0
Order By: Relevance
“…Parks are encouraging sites for promoting PA because their provision and management can be influenced through public policy (10,53), but all groups do not always have equal access to policy making processes (54). Unlike many other park audit tools, the CPAT was designed with and for nonresearchers as a user-friendly yet reliable instrument that could be incorporated into community evaluation and advocacy efforts (34).…”
Section: Limitationsmentioning
confidence: 99%
“…Parks are encouraging sites for promoting PA because their provision and management can be influenced through public policy (10,53), but all groups do not always have equal access to policy making processes (54). Unlike many other park audit tools, the CPAT was designed with and for nonresearchers as a user-friendly yet reliable instrument that could be incorporated into community evaluation and advocacy efforts (34).…”
Section: Limitationsmentioning
confidence: 99%
“…Community size and heterogeneity can also affect participatory processes. Communities that have undergone rapid change, including demographic shifts, have lower community capacity (Feudenberg et al 2011), not least because networks and social ties have been disrupted. Collective action theory predicts an inverted U-shaped relationship between population size and successful community resource management, with small populations unable to absorb the transaction costs associated with participation and large populations suffering prohibitively high barriers to entry (Brooks et al 2012).…”
mentioning
confidence: 99%
“…The sense of community, including feelings of connection, support, and collective problem solving, plays a key role in shaping the capacity of a community to engage. Such capacity also depends upon community leaders and the strength of social and organizational networks (Feudenberg et al 2011), adequate resources, including financial resources (Bisset 2000), and the presence of bridging capacities, i.e., the capacity of groups to link with others, particularly across communities (Putnam 1993). Community capacity is not given, but stems from the cumulative effect of previous actions, creating social obligation but also requiring in turn some social stability.…”
mentioning
confidence: 99%
“…Meanwhile, other scholars criticized the concept of delegating too much autonomy to locals, because it may create community segregation and instability, favor the haves over the havesnot, and cause ineffective and costly decision-making [11]- [13]. Community involvement in decision-making is also studied in the field of natural resources and environmental decision-making [14], [15] and energy planning and development [16]- [18]. These studies showed that the community level is an interesting object of study, especially related to decision-making in the energy-environmental field.…”
Section: Introductionmentioning
confidence: 99%